Identifikasi Penerapan Holistik Intergratif pada Aspek Seni di TK PKK Tamansatriyan Malang - Rizki, Silfia Novita; Pamungkas, Joko (JURNAL ILMU PENDIDIKAN, 2022)
This article aims to determine the application of holistic integrative terms from the artistic aspect which consists of the implementation of educational services arranged with art programs that develop other aspects such as moral and religious values, language, cognitive, social, and physical motor skills in TK PKK Tamansatriyan Malang. Data collection techniques through interviews, documentation, and observation. The sources of data in this study were principals who were interviewed, students who were observed, teachers who were interviewed and observed, parents, foundations, and employees who the authors determined based on the considerations of the principal, documents, and archives at the school that supports the main data source. The application of holistic integrative in early childhood education at TK PKK Tamansatriyan Malang in terms of the artistic aspect has been carried out well. Through various programs in the arts aspect, which can be seen from fashion shows, creative dances, fine arts and crafts, and even traditional dances, besides cultural introductions through traditional foods. In the programs, parents and the village also take part in the preparation of the program to be implemented.